Letramento digital: a prática de leitura e de escrita mediada pelo Blog - Oliveira, Flávia Sirino de (2014)
Through this research, goal suggest how to use the blog in Portuguese Language classes in Secondary School, while resource and pedagogical strategy in the development of digital literacy. I seek to accomplish this through the following specific objectives: to propose the use of educational blog in Portuguese Language classes; Report the experiences of using educational blog, "Reading Liberta", in mediating the teaching-learning process; Understand how the pedagogical ideas of learning are designed and incorporated into the construction and use of blogs. The blog "Reading Liberta" was created on July 28, 2010, and, from the beginning, thought to be collaborative, educational and interactive. The work done in this digital environment are guided by educational projects. The research was applied in EMEF Leonidas Santiago, located in Rangel district, in João Pessoa-PB, with 118 students. Regarding methodological procedures, bibliographic and ethnographic study utilized. The qualitative approach enabled the cooperative and interactive engagement between the researcher and the object of study. I chose to work with the blog by it to enable the student to a collective work, permitting the construction of new knowledge. As for the results, I observed, among others, that students have acquired skills and autonomy that allowed them to deal with issues relating to visual design, interaction and navigation and learned to make use of cognitive and metacognitive strategies that allowed the direction, organization, monitoring and critical evaluation of knowledge construction in cyberspace. So the blog is an environment that enables discussions, fosters communication, democratization of ideas, disseminates information and provides the seizure of knowledge with freedom of expression.